Penerapan multimedia interaktif pada materi sistem pendingin untuk meningkatkan hasil belajar siswa - Nofiandri, Ernal (Indonesian Journal of Educational Development (IJED), 2021)
This study aims to determine the increase in student learning outcomes in Cooling System Material by implementing interactive multimedia in learning, namely Learning Videos and interactive presentations. This research is a Classroom Action Research (CAR) which consists of 2 cycles. The subjects of this research were students of class XI TKRO SMK Negeri 1 Calang consists of 18 people. Data obtained from student learning outcomes using tests. From the data analysis with the application of the use of multimedia, in the first cycle the average student learning outcomes were 61.11% and in the second cycle the average student learning outcomes were 94.44%. This shows that the average achievement increased from the pre-cycle 44.44% and in cycle 1 to 61.11% and in cycle II to 94.44%. Overall student learning outcomes in accordance with the pass threshold criteria for student productive learning are said to be complete. That way it can be said that learning by applying multimedia to the cooling system material can be said to be successful. The results of this study prove that the application of multimedia can increase the activity and learning outcomes of the Class XI TKRO Student in SMK Negeri 1 Calang for the 2019/2020 academic year. Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar siswa pada materi Sistem Pendingin dengan menerapkan multimedia interaktif dalam pembelajaran yaitu video pembelajaran dan presentasi interaktif. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang terdiri dari 2 siklus. Subjek penelitian ini adalah siswa kelas XI TKRO SMK Negeri 1 Calang Tahun Pelajaran 2019/2020 yang berjumlah 18 orang. Data diperoleh dari hasil belajar siswa yang dilakukan dengan mengunakan tes. Dari analisis data dengan penerapan Penggunaan Multimedia, pada siklus I rata-rata hasil belajar siswa sebesar 61,11% dan pada siklus II rata-rata hasil belajar siswa sebesar 94,44%. Ini menunjukkan rata-rata prestasi meningkat dari prasiklus hanya 44,44%, pada siklus I menjadi 61,11% dan pada siklus II menjadi 94,44%. Secara keseluruhan hasil belajar siswa sesuai dengan kriteria batas lulus pembelajaran produktif siswa dikatakan tuntas. Dengan begitu dapat dikatakan pembelajaran dengan menerapkan Multimedia pada materi Sistem Pendingin dapat dikatakan berhasil. Hasil penelitian ini membuktikan bahwa penerapan multimedia dapat meningkatkan aktivitas dan hasil belajar Materi Sistem Pendingin Siswa Kelas XI TKRO SMK Negeri 1 Calang Tahun Pelajaran 2019/2020.